Body mass scaling of frontal area in competitive cyclists not using aero-handlebars - Heil, D. P. (European Journal of Applied Physiology, 2002)
This study was designed to evaluate the scaling relationship between body mass (mb) and projected frontal area (AP) in competitive male cyclists using traditional drop-style handlebars. A group of 21 male cyclists [mean (SD) mb 74.4 (7.2) kg, height 1.82 (0.06) m, age 23.6 (5.1) years] had AP determined from photographs taken while seated on their own racing bicycles in four body positions: (1) stem position; (2) brake hoods position; (3) drops position; (4) traditional aero-position. For each position, AP for the body of the cyclist (Body AP), as well as the cyclist and his bicycle (Total AP), were determined. Body AP was significantly smaller than Total AP in all four positions by a nearly constant bicycle AP of 0.117-0.124 m2. Using multiple log-linear regression analysis procedures, prediction equations were developed for both Body AP and Total AP (dependent variables) using a cluster of binary-coded variables to indicate body position and mb as independent variables (n=88 observations). The regression analysis revealed that Body AP scaled with mb to the +0.720 power [95% confidence interval (CI): 0.585-0.855], which did not differ significantly from the +0.762 exponent reported previously for Body AP whilst using aero-handlebars. In contrast, Total AP scaled with mb to the +0.594 power (95% CI: 0.468-0.720) which was significantly lower than +0.762 exponent reported previously. The lower exponent for Total AP is explained by the nearly constant contribution of the bicycle AP to Total AP (mean bicycle AP=0.122 m2). These data help to explain the determinants of AP and aerodynamic drag in competitive male cyclists who use the traditional body postures.